The impact of carbon pricing in a multi-region production network model and an application to climate scenarios - Ivan Frankovic (Deutsche Bundesbank, 2022)
This paper builds on existing production network models to study the impact of global and sub-global carbon pricing. It uses the World Input-Output Database (WIOD) to calibrate intersectoral trade between seven regions and 56 economic sectors per region as well as EXIOBASE's sectoral accounts of greenhouse gas emissions to calibrate emission costs per sector for a given carbon price. The latter taxes emissions associated with the intermediate and final demand of fossil fuels as well as other emissions inherent to production. The global setup of the model allows the international propagation of carbon prices to be analyzed along worldwide value chains. The simulated sectoral impacts of carbon taxes are highly heterogeneous across sectors and regions, with the agricultural, mining, fossil fuel processing and transport sector exhibiting the largest impacts across all regions. For several sectors in Germany and Europe, particularly manufacturing sectors, international spillovers from carbon pricing outside of Europe can be substantial and increase value added losses by up to 100% relative to the impact of European-only carbon prices. The paper furthermore outlines a simple approach for applying the sectorally disaggregated results to global climate scenarios.
Keywords: D57; E23; H23; Q54; 330; climate scenarios; carbon pricing; input-output data; production network models